Sustainable and Mild Catalytic Acceptorless Dehydrogenations - Jagtap, Rahul A.; Kanai, Motomu (Synlett, 2023)
Catalytic acceptorless dehydrogenation of organic molecules plays a crucial role in fine-chemical synthesis as well as in energy storage and transport. In particular, the acceptorless dehydrogenation of saturated N-heteroarenes and hydrocarbons is realized by both transition-metal-free and transition-metal-catalyzed approaches. In this direction, our research group aims to develop mild catalytic acceptorless dehydrogenation protocols, in the main by using photoredox approaches. In this account, we briefly discuss the advances made by our group on the dehydrogenation of saturated N-heterocycles, aliphatic alcohols, and relatively challenging hydrocarbons.1 Introduction1.1 Challenges Associated with Catalytic Acceptorless Dehydrogenation2 Transition-Metal-Free Dehydrogenation of N-Heterocycles3 Photoinduced Hybrid-Catalysis-Enabled Dehydrogenations3.1 The Binary Catalyst System3.2 The Ternary Catalyst System3.3 The Noble-Metal-Free Catalyst System3.4 Catalytic Acceptorless Dehydrogenation of Aliphatic Alcohols4 Self-Photo-Sensitizing Hydrogen Atom Transfer Catalysis5 Summary
Keywords: catalytic acceptorless dehydrogenation; photoredox catalysis; hybrid catalysis; transition-metal catalysis; hydrogen atom transfer; heterocycles; hydrocarbons; alcohols